Population Pharmacokinetic Model for the Use of Intravenous or Subcutaneous Infliximab in Patients with Inflammatory Bowel Disease: Real-World Data from a Prospective Cohort Study - Joo Hye Song; Sung Noh Hong; Myeong Gyu Kim; Minjung Kim; Seong Kyung Kim; Eun Ran Kim; Dong Kyung Chang; Young-Ho Kim (Gut and Liver)
Background/Aims: Infliximab treatment failure in patients with inflammatory bowel disease may result from sub-optimal infliximab trough level. An understanding of pharmacokinetics (PKs) is important to maintain an optimal trough level. PK studies of the switch to subcutaneous (SC) infliximab from intravenous (IV) infliximab using real-world data are lacking. We aimed to develop a population PK model of IV and SC infliximab to predict individual infliximab exposure during maintenance therapy. Methods: We used data from prospectively collected data on IV and SC infliximab concentrations in patients with inflammatory bowel disease receiving maintenance treatment from February 2020 to December 2022 at Samsung Medical Center. Population PK analysis was conducted by using a two-compartment model with first-order absorption and first-order elimination. Goodness-of-fit plots and visual predictive check were used to evaluate the PK model. Results: A total of 2,132 samples from 181 patients (149 Crohn’s disease and 32 ulcerative colitis) were analyzed. We developed an infliximab population PK model using body mass index, albumin, C-reactive protein level, and the anti-drug antibody level and validated its predictive performance. Conclusions: It may be possible to predict the infliximab trough level of both IV and SC infliximab in patients with inflammatory bowel disease during maintenance treatment by using our model in real-world practice.